2013
DOI: 10.1201/b14859-5
|View full text |Cite
|
Sign up to set email alerts
|

Can We Predict Every Spike?

Abstract: Is it possible to predict the spike times of a neuron with millisecond precision? In the classical picture of rate coding (Adrian, 1928), single spikes do not play a role, and the question would have to be answered negatively. For rate coding in a singleneuron, the relevant quantity to encode a stimulus such as pressure onto a touch sensor in the skin (Adrian, 1928) or presence of a light bar in the receptive field of a visual neuron (Hubel and Wiesel, 1959) is the number of spikes a neuron emits in a short ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The predicted spike trains achieved an averaged coincidence rate of 50%. The scaled coincidence rate obtained by dividing by the intrinsic reliability (Jolivet et al, 2008a ; Naud and Gerstner, 2012 ) was 72%, which is comparable to the state-of-the performance for purely somatic current injection which reaches up to 76% (Naud et al, 2009 ). Comparing with a passive model for dendritic current integration, we found that the predictive power decreased to a scaled coincidence rate of 53%.…”
Section: Discussionmentioning
confidence: 66%
“…The predicted spike trains achieved an averaged coincidence rate of 50%. The scaled coincidence rate obtained by dividing by the intrinsic reliability (Jolivet et al, 2008a ; Naud and Gerstner, 2012 ) was 72%, which is comparable to the state-of-the performance for purely somatic current injection which reaches up to 76% (Naud et al, 2009 ). Comparing with a passive model for dendritic current integration, we found that the predictive power decreased to a scaled coincidence rate of 53%.…”
Section: Discussionmentioning
confidence: 66%
“…Finally, we find that both the intrinsic (membrane conductance) and response (STA, FI) properties of excitatory neurons are more heterogeneous, compared to inhibitory neurons. [22,24,[35][36][37][38][39][40][41][42][43][44][45] and the heterogeneity in such cell properties has been investigated in excitatory (but not inhibitory) cells [46]. With this manuscript, we add a functional dimension to these basic properties of cortical spike initiation: We show how different mechanistic features of cortical cells can influence their information transfer and binary classification.…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…It has been shown repeatedly, that the spiking behaviour of cortical neurons can be fitted relatively well with a simple threshold model with an extra feedback variable [22,24,[67][68][69][70][71][72][73][74][75][76][77].…”
Section: Plos Computational Biologymentioning
confidence: 99%